Rediscovery and redescription of Dixonius siamensis (Boulenger, 1899) (Squamata: Gekkonidae), type species of the genus, with lectotype designation - Pauwels, Olivier S. G.; Das, Sunandan; Brecko, Jonathan; Bringsøe, Henrik; Sumontha, Montri (Zootaxa, 2024)
We redescribe the type material of Phyllodactylus siamensis Boulenger, 1899, type species of the Southeast Asian gekkonid genus Dixonius Bauer, Good & Branch, 1997, using external morphology and cranial osteology. There is some evidence that the type series contains more than one species; we hence designate a lectotype in order to stabilize nomenclature and provide more precision on the geographical location of the type locality. Because the current concept of Dixonius siamensis auctorum is incomplete and composite, we provide a revised diagnosis based on the presently designated lectotype and a paralectotype from the same locality, as well as observations on new material from the type locality and the first photographs of live topotypical individuals. We regard Dixonius siamensis as probably geographically restricted to the Dong Phaya Yen mountain range in central Thailand, and the numerous published mentions of this species from outside this range likely refer to other or undescribed taxa. We treat Phyllodactylus burmanicus Annandale, 1905 from Tavoy, southern Myanmar, as a valid species, as Dixonius burmanicus comb. nov.